A step towards sustainable aquaculture: Multiobjective feed formulation reduces environmental impacts at feed and farm levels for rainbow trout - Aurélie Wilfart; Florence Garcia-Launay; Frederic Terrier; Espoir Soudé; Pierre Aguirre; Sandrine Skiba-Cassy (Aquaculture, 2023)

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Frankenstein Ecosystems and 21st Century Conservation Agendas: Reply to Oliveira‐Santos and Fernandez - Philip J. Seddon; Mark Stanley Price; Frederic Launay; Mike Maunder; Pritpal Soorae; Sanjay Molur; Doug Armstrong; Mike Jordan; Sarah Dalrymple; Piero Genovesi (Conservation Biology, 2011)

The Risks of Assisted Colonization - Philip J. Seddon; Doug P. Armstrong; Pritpal Soorae; Frederic Launay; Sally Walker; Carlos R. Ruiz‐Miranda; Sanjay Molur; Heather Koldewey; Devra G. Kleiman (Conservation Biology, 2009)